Effects of letrozole on biochemical markers of bone and liver - Yonden, Z.; Aydin, M.; Alcin, E.; Yilmaz, B. (Amer Assoc Clinical Chemistry, 2008)
[Abstract Not Available]
60th Annual Meeting of the American-Association-for-Clinical-Chemistry -- JUL 27-31, 2008 -- Washington, DC